Effect of natural accelerated growth in the per- formance of buffalo calves in a dual-purpose production system - Luis Mantilla; Omar Castellano; Rubiela Rodríguez (Revista Científica)
The objective of this work was to evaluate the effect of implementing a system of naturally accelerated growth in crossbreed buffalo calves in a dual-purpose production system in Hato Los Olivos, Barinas, Venezuela. The crossbreed buffaloes in the trial descend mainly from Murrah, Mediterranean and Buffalypso. The dual-purpose system is based on selling weaning calves by using milk to raise the calves and help to cover daily expenses. A total of 79 female and 67 male buffalo calves born between November and January were randomly divided into two groups to apply different treatments. The first group (T1) went under the farm’s traditional management system (the buffalo cow and the calf enter the milking parlour 15 days after calf birth, leaving a milk quarter for the calf to feed). The other calves underwent a system of management (T2) which we call “growth flare”, that proposes natural accelerated growth in buffalo calves: the buffalo cow and the calf remain together without going to the milking parlour until the thoracic perimeter of the calf reaches 100 cm. From that moment, the buffalo calf goes to the milking parlour to stimulate the milk let-down reflex. Results showed that the percentage of mortality for T1 was 13%, whereas for T2, it was 2%. The weaning average weight in T1 was 134 Kg for females and 141 Kg for males. In T2, females reached 192 Kg and males 206 Kg. The heifer’s first breeding was, on average, 36 months for T1 and 24 months for T2. The average age at slaughter was 46 months for T1 and 27 months for T2. The animals from T2 showed more than 60 Kg in average weaning weight gain compared with those of the traditional treatment (T1) and reduced mortality in the milking parlour of 2%. This impacts a heifer’s first breeding and age at slaughter, optimizing the buffalo’s dual-purpose breeding in the western plains of Venezuela. The system T2 required less use of medicines, which may help to reach a more sustainable development system. It is an unfinished trial that has been going on over the last four years, and we are still evaluating the results. However, accelerated growth in calves is an excellent alternative to reduce costs, resulting in a mortality decrease; the weaning weight gain compensates for the cost of the milk consumed by the calf in the first two months of lactation. Developing a buffalo weight measuring tape (weigh band) is also highly recommended to simplify weight measuring in the fieldwork.